The worldwide Alzheimer's disease neuroimaging initiative: an update - Hendrix, James A. (2015)
The Alzheimer's Disease Neuroimaging Initiative (ADNI), launched in 2004, has worked to accelerate drug development by validating imaging and blood/cerebrospinal fluid biomarkers for Alzheimer's disease clinical treatment trials. ADNI is a naturalistic (nontreatment) multisite longitudinal study. A true public-private partnership, the initiative has set a new standard for data sharing without embargo and for the use of biomarkers in dementia research. The ADNI effort in North America is not the only such effort in the world. The Alzheimer's Association recognized these global efforts and formed Worldwide ADNI (WW-ADNI). By creating a platform for international collaboration and cooperation, WW-ADNI's goals are to harmonize projects and results across geographical regions and to facilitate data management and availability to investigators around the world. WW-ADNI projects include those based in North America, Europe, Japan, Australia, Korea, and Argentina.